Impact of collateralisation to a concomitant chronic total occlusion in patients with ST-elevation myocardial infarction: a subanalysis of the EXPLORE randomised controlled trial. Issue 2 (16th July 2018) - van Dongen, Ivo M; Elias, Joëlle; van Houwelingen, K Gert; Agostoni, Pierfrancesco; Claessen, Bimmer E P M; Hoebers, Loes P; Ouweneel, Dagmar M; Scheunhage, Esther M; Delewi, Ronak; Piek, Jan J; Råmunddal, Truls; Laanmets, Peep; et al.
Abstract : Objective: The impact on cardiac function of collaterals towards a concomitant chronic total coronary occlusion (CTO) in patients with ST-elevation myocardial infarction (STEMI) has not been investigated yet. Therefore, we have evaluated the impact of well-developed collaterals compared with poorly developed collaterals to a concomitant CTO in STEMI. Methods and results: In the EXPLORE trial, patients with STEMI and a concomitant CTO were randomised to either CTO percutaneous coronary intervention (PCI) or no-CTO PCI. Collateral grades were scored angiographically using the Rentrop grade classification. Left ventricular ejection fraction (LVEF) and left ventricular end-diastolic volume (LVEDV) at 4 months were measured using cardiac magnetic resonance imaging. Well-developed collaterals (Rentrop grades 2–3) to the CTO were present in 162 (54%) patients; these patients had a significantly higher LVEF at 4 months (46.2±11.4% vs 42.1±12.7%, p=0.004) as well as a trend for a lower LVEDV (208.2±55.7 mL vs 222.6±68.5 mL, p=0.054) when compared with patients with poorly developed collaterals to the CTO. There was no significant difference in the total amount of scar in the two groups. Event rates were statistically comparable between patients with well-developed collaterals and poorly developed collaterals to the CTO at long-term follow-up. Conclusions: In patients with STEMI and a concomitant CTO, the presence of well-developed collaterals to a concomitant CTO is associated with a better LVEF at 4 months. However, this effect on LVEF did not translate into improvement in clinical outcome. Therefore, the presence of well-developed collaterals is important, but should not solely guide in the clinical decision-making process regarding any additional revascularisation of a concomitant CTO in patients with STEMI. Clinical trial registration: NTR1108.